The Basally Expressed p53-Mediated Homeostatic Function - Nagpal, Isha; Yuan, Zhi-Min (Frontiers in Cell and Developmental Biology, 2021)
Apart from mutations in the p53 gene, p53 functions can be alternatively compromised by a decrease in nuclear p53 protein levels or activities. In accordance, enhanced p53 protein turnover due to elevated expression of the critical p53 E3 ligase MDM2 or MDM2/MDMX is found in many human cancers. Likewise, the HPV viral E6 protein-mediated p53 degradation critically contributes to the tumorigenesis of cervical cancer. In addition, growth-promoting signaling-induced cell proliferation is accompanied by p53 downregulation. Animal studies have also shown that loss of p53 is essential for oncogenes to drive malignant transformation. The close association between p53 downregulation and carcinogenesis implicates a critical role of basally expressed p53. In accordance, available evidence indicates that a reduced level of basal p53 is usually associated with disruption of homeostasis, suggesting a homeostatic function mediated by basal p53. However, basally expressed p53 under non-stress conditions is maintained at a relatively low abundance with little transcriptional activity, raising the question of how basal p53 could protect homeostasis. In this review, we summarize the findings pertinent to basal p53-mediated activities in the hope of developing a model in which basally expressed p53 functions as a barrier to anabolic metabolism to preserve homeostasis. Future investigation is necessary to characterize basal p53 functionally and to obtain an improved understanding of p53 homeostatic function, which would offer novel insight into the role of p53 in tumor suppression.